2021
DOI: 10.1088/1361-648x/abdc8f
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of empirical interatomic potential to predict thermal conductivity in ThO2 and UO2

Abstract: Computing vibrational properties of crystals in the presence of complex defects often necessitates the use of (semi-)empirical potentials, which are typically not well characterized for perfect crystals. Here we explore the efficacy of a commonly used embedded-atomempirical interatomic potential for the U x Th1−x O2 system, to compute phonon dispersion, lifetime, and branch specific thermal conductivity. Our approach for ThO2 involves using lattice dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…The non-analytical correction of the Born charge effect was also included in the phonon calculations to account for LO-TO splitting. For SCAN calculations, the macroscopic dielectric constant and Born effective charges were κ = 4.482, Z ⋆ T h = 5.317, and Z ⋆ O = −2.673; for EIP calculations, the particle charges in EIP were taken as Born effective charges (Z ⋆ T h = q T h and Z ⋆ O = q O ), and the dielectric constants were fitted to reproduce the phonon frequency of the highest longitudinal optical mode (denoted LO2 [38]) at the Γ point. The fitted dielectric constants were ǫ = 0.86 for the CRG and ǫ = 0.90 for the PW, respectively.…”
Section: Training and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-analytical correction of the Born charge effect was also included in the phonon calculations to account for LO-TO splitting. For SCAN calculations, the macroscopic dielectric constant and Born effective charges were κ = 4.482, Z ⋆ T h = 5.317, and Z ⋆ O = −2.673; for EIP calculations, the particle charges in EIP were taken as Born effective charges (Z ⋆ T h = q T h and Z ⋆ O = q O ), and the dielectric constants were fitted to reproduce the phonon frequency of the highest longitudinal optical mode (denoted LO2 [38]) at the Γ point. The fitted dielectric constants were ǫ = 0.86 for the CRG and ǫ = 0.90 for the PW, respectively.…”
Section: Training and Validationmentioning
confidence: 99%
“…Multiple studies have applied MD to simulate thermal transport of pure ThO 2 and ThO 2 with various defects [34][35][36][37], by using the CRG potential, an EIP developed by Cooper et al [20], fitted to experimental measurements. Recently, Jin et al [38] carefully assessed the accuracy of phonon property predictions using DFT-BTE and the CRG potential, showing that the CRG exhibits disagreement with the experimental phonon spectra of optical branches as well as with thermal conductivity. By training a new EIP for ThO 2 and validating the EIP through comparison to phonon properties, we aim to both demonstrate our EIP training approach using IDs, and to support future MD studies on thermal transport in ThO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The next level of approximation is directly computing the cubic phonon interactions from first principles, computing the phonon lifetimes from perturbation theory, and then using the RTA. This has been executed for ThO2 using DFT [151,152] and UO2 using DFT+U [27], where the latter demonstrated rather substantial deviation from experiment. The next level of approximation goes beyond the RTA and fully solves the BTE, which has been executed for ThO2 [153,154].…”
Section: First-principles Calculations Of Uo2 and Tho2mentioning
confidence: 99%
“…Recently, the CRG [923] potential was rigorously accessed for accurate predictions of phonon dispersion, lifetime, and branch specific conductivity for UO2 and ThO2 [152]. It was found that the CRG potential captures the dispersion of the acoustic branches well, but exhibits significant discrepancies for the optical branches, leading to an overestimate of phonon lifetime and conductivity for both materials.…”
Section: Bulk Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation